2018
DOI: 10.1159/000484223
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fecal Markers with Magnifying Endoscopic Stratification in Patients with Ulcerative Colitis Who Are in Clinical Remission

Abstract: Background: Maintenance of mucosal healing is recommended during the treatment of ulcerative colitis (UC). However, symptoms of UC often do not reflect mucosal disease activity. Fecal markers such as calprotectin, lactoferrin, and hemoglobin have been reported to correlate well with the Mayo endoscopic subscore (MES) and are being considered alternative monitoring tools in endoscopy. Ulcerative Colitis Endoscopic Index of Severity (UCEIS) is a new and more detailed endoscopic scoring system compared to MES. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Systemic inflammation caused by these diseases may lead to subclinical gut inflammation and consequent occult bleeding. This hypothesis is supported by recent studies in which f-Hb was reported to be a useful marker of gut inflammation in patients with ulcerative colitis in clinical remission [23,24]. In addition, systemic inflammation has been reported to be associated with mortality.…”
Section: Discussionsupporting
confidence: 52%
“…Systemic inflammation caused by these diseases may lead to subclinical gut inflammation and consequent occult bleeding. This hypothesis is supported by recent studies in which f-Hb was reported to be a useful marker of gut inflammation in patients with ulcerative colitis in clinical remission [23,24]. In addition, systemic inflammation has been reported to be associated with mortality.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it may be that the increased risk of colonic adenoma in the gFOBT positive population is due to generalised colonic inflammation rather than bleeding from the adenomas themselves. This concept is supported by recent work on mucosal healing in inflammatory bowel disease, in which f-Hb has been found to be a better marker than the more traditional measure of gut inflammation, faecal calprotectin 19 20…”
Section: Discussionmentioning
confidence: 79%
“…Since infiltration of neutrophils during intestinal inflammation results in the release of calprotectin in stools, termed FC, its level is well correlated to mucosal activity in UC patients [39][40][41][42][43]. In particular, FC level is considered to be an effective surrogate marker for evaluating mucosal healing in UC patients in clinical remission [44,45].…”
Section: Fecal Calprotectin Levelmentioning
confidence: 99%